Design and Impact of Interactive Video Content for the Improvement of Student Engagement and Learning - Priyakanth, R.; Abburi, Radha; Praveena, Manne (Journal of Engineering Education Transformations, 2021)
All over the world online education is offered now in all the streams. Numerous new technology courses in the form of video lectures are available online. However, in the engineering stream, questions arise about real learning. This study explores the new ways of making the video content more interactive in such a way that the learners will be active, engage themselves, participate, respond, and improve their thinking skills. Interactive video content can comprise a wide range of active elements, including questions, polls, interactive summaries, and many more. Including the interactive training videos in the learning management system (LMS) in any course may bring a lot of change in the learners’ perspective of processing the attained knowledge. As a part of the study, the interactive videos on working in MATLAB environment were uploaded into the LMS portal of a lab course and the participation and engagement of around 120 learners was examined by the way the questions were answered. The questions in the form of case studies were given at middle to higher levels of learning classified by Bloom’s Taxonomy. The attained learning outcomes measured indicated improvement in the learners’ adaptation to new programming languages, skills they acquired in analyzing the case studies. New technologies like H5P etc for making interactive videos assuredly help in the acquisition and enhancement of new skill sets of the learner as evident in the observations. These interactions helps us in driving deeper engagement and transform the ways a learner thinks and processes the knowledge attained.